THE INTERPRETATION OF SURAH AL-MA’UN: AN TEMATIC STUDY - Kuthar Gabar Zedin Alle (STAI Al-Hamidiyah Bangkalan, 2024)
This study examines the interpretation of Surah Al-Ma’un using an objective methodology aimed at shedding light on the profound meanings and lessons derived from this chapter. The study begins with an introduction to the Surah, which is one of the short Meccan chapters containing powerful messages related to social ethics and responsibility toward others. The study focuses on analyzing the vocabulary and linguistic structures in the Surah, such as the meaning of